Neurocognitive profiles in adolescents and young adults with congenital heart disease [Perfis neurocognitivos em adolescentes e jovens adultos com cardiopatias congénitas] - Areias, ME (2018)
Introduction and Objectives: The objectives of this study were to assess the neuropsychological performance (NP) of adolescents and young adults with congenital heart disease (CHD), comparing them with a group of healthy controls, to determine whether there are different neurocognitive phenotypes in CHD, and to identify their relation to sociodemographic, neonatal, clinical and psychological adjustment variables. Methods: A total of 217 CHD patients (116 male, aged 15.73±2.68 years) and 80 controls (35 male, age 16.76±2.22 years) underwent an extensive neuropsychological assessment and analysis of psychological adjustment. Results: CHD patients had significantly poorer NP than healthy controls in all neurocognitive domains. Three different phenotypes of NP in CHD patients were identified: non-impaired (NI), moderately impaired (MI) and globally impaired (GI). They differed in all dimensions of NP. The GI cluster showed fewer years of schooling (p=0.025) and lower neonatal indicators such as head circumference (p=0.019), 1-min Apgar score (p=0.006), birth weight (p=0.05) and length (p=0.034) than the NI cluster. In the MI and GI clusters, there were more cyanotic forms of disease, including tetralogy of Fallot and transposition of the great arteries. The GI cluster presented more difficulties with psychological adjustment, including social (p=0.038), attention (p=0.001) and aggressive (p=0.003) problems. Conclusions: CHD patients have poorer NP than controls. NP in the CHD group can be classified in three clusters that reflect different levels of neuropsychological functioning, which is sensitive to social, neonatal and psychological adjustment variables. (c) 2018 Sociedade Portuguesa de Cardiologia